2021
DOI: 10.3390/ijms22020483
|View full text |Cite
|
Sign up to set email alerts
|

Camphor and Eucalyptol—Anticandidal Spectrum, Antivirulence Effect, Efflux Pumps Interference and Cytotoxicity

Abstract: Candidaalbicans represents one of the most common fungal pathogens. Due to its increasing incidence and the poor efficacy of available antifungals, finding novel antifungal molecules is of great importance. Camphor and eucalyptol are bioactive terpenoid plant constituents and their antifungal properties have been explored previously. In this study, we examined their ability to inhibit the growth of different Candida species in suspension and biofilm, to block hyphal transition along with their impact on genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 54 publications
2
33
0
1
Order By: Relevance
“…At ¼ MBIC 90 , CBD produced upregulation of yeast-associated genes and downregulation of hyphae-specific genes. As reported by Ivanov et al [ 166 ], camphor inhibited more than 50% of the biofilm biomass in C. albicans strains at 62–250 µg/mL, while in C. tropicalis, the inhibition was achieved at 175 µg/mL. On the other hand, eucalyptol showed the same effect in the tested C. albicans strains at higher concentrations (>3000 µg/mL) and in C .…”
Section: Reported Antibiofilm Activities Of Pure Natural Compoundssupporting
confidence: 73%
See 1 more Smart Citation
“…At ¼ MBIC 90 , CBD produced upregulation of yeast-associated genes and downregulation of hyphae-specific genes. As reported by Ivanov et al [ 166 ], camphor inhibited more than 50% of the biofilm biomass in C. albicans strains at 62–250 µg/mL, while in C. tropicalis, the inhibition was achieved at 175 µg/mL. On the other hand, eucalyptol showed the same effect in the tested C. albicans strains at higher concentrations (>3000 µg/mL) and in C .…”
Section: Reported Antibiofilm Activities Of Pure Natural Compoundssupporting
confidence: 73%
“…On the other hand, eucalyptol showed the same effect in the tested C. albicans strains at higher concentrations (>3000 µg/mL) and in C . tropicalis , C. parapsilosis and C. krusei at >1000 µg/mL [ 166 ]. Camphor, applied at 125 µg/mL, reduced ROS generation in one strain of C. albicans , although eucalyptol failed to exert this effect.…”
Section: Reported Antibiofilm Activities Of Pure Natural Compoundsmentioning
confidence: 99%
“…Moreover, sesquiterpenoids have also been reported to have anti-inflammatory [ 27 ] and neuroprotective effects [ 28 ]. Previous studies have shown that Baltic amber contains several different active compounds [ 16 , 29 ], such as p-cymene and dehydroabietic acid, which have been reported to have anti-inflammatory effects [ 30 , 31 ]; camphor, which has been reported to have antifungal activity [ 32 ]; pimaric acid, which has been reported to have anti-atherosclerotic activity [ 33 ], etc. However, there are still many other unknown components in amber, and future studies should focus on identifying all components of the amber extract and elucidating the exact components that have potential neuroprotective effects.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-hyphal potential of camphor (0.125 mg/mL) and eucalyptol (23 mg/mL) against clinical isolate of C. albicans were evaluated [ 66 ]. Both compounds triggered a marked decrease in the number of hyphal cells and block hyphal transition along with antibiofilm properties.…”
Section: Recent Update On Antifungal Targets and Strategiesmentioning
confidence: 99%